2018
DOI: 10.1002/open.201800156
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Molecular Frameworks of Farnesoid X Receptor Modulators by Ensemble Machine Learning

Abstract: The bile acid activated transcription factor farnesoid X receptor (FXR) has revealed therapeutic potential as a molecular drug target for the treatment of hepatic and metabolic disorders. Despite strong efforts in FXR ligand development, the structural diversity among the known FXR modulators is limited. Only four molecular frameworks account for more than 50 % of the FXR modulators annotated in ChEMBL. Here, we leverage machine learning methods to expand the chemical space of FXR‐targeting small molecules by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 39 publications
(79 reference statements)
0
3
0
Order By: Relevance
“…For example, the Schneider group previously developed a SOM-based prediction of drug equivalence relationships (SPiDER) software, which tessellates a reference ligand space and predicts targets for new compounds based on assigning them to a particular winner neuron, then performing consensus scoring and statistical analysis to estimate the pseudoprobability of activity against a range of targets. Building on the success of this approach, the SOM concept was extended by the same group for many different tasks, grouping molecules with similar pharmacophoric features into clusters of functionally related compounds to generate target predictions which were then experimentally validated. In addition, a similar technology, the counter-propagation ANN (CP-ANN), was used in a publication by Merk et al to identify novel modulators of the farnesoid X receptor, based on a combined approach using k NN and pharmacophoric screening. This study demonstrated the power of this approach for introducing useful ordering and segmentation of chemical spaces.…”
Section: Artificial Intelligence Approaches In Ligand-based Virtual S...mentioning
confidence: 99%
“…For example, the Schneider group previously developed a SOM-based prediction of drug equivalence relationships (SPiDER) software, which tessellates a reference ligand space and predicts targets for new compounds based on assigning them to a particular winner neuron, then performing consensus scoring and statistical analysis to estimate the pseudoprobability of activity against a range of targets. Building on the success of this approach, the SOM concept was extended by the same group for many different tasks, grouping molecules with similar pharmacophoric features into clusters of functionally related compounds to generate target predictions which were then experimentally validated. In addition, a similar technology, the counter-propagation ANN (CP-ANN), was used in a publication by Merk et al to identify novel modulators of the farnesoid X receptor, based on a combined approach using k NN and pharmacophoric screening. This study demonstrated the power of this approach for introducing useful ordering and segmentation of chemical spaces.…”
Section: Artificial Intelligence Approaches In Ligand-based Virtual S...mentioning
confidence: 99%
“…Both studies present high predictive accuracy with area under the ROC curve values reaching 0.8. The third study focus on different machine learning methods (counter-propagation artificial neural network, similarity of 3D pharmacophore feature distributions method and k-nearest neighbor learner) that were optimized and combined to identify new FXR modulators molecular frameworks ( 62 ). This ensemble machine learning approach was used in a prospective screening of 3 million commercially available compounds and enable the discovery of 4 new experimentally validated FXR agonist and 2 FXR antagonist compounds with original molecular frameworks.…”
Section: Studied Nuclear Receptorsmentioning
confidence: 99%
“…One application of machine learning is quantitative structure-activity relationship (QSAR) modeling, which is based on the premise that the molecular structure is responsible for the molecule bioactivity and links molecular descriptors to experimentally-determined molecular properties with machine learning algorithms. [17][18][19][20][21] Compared to the 'direct' QSAR approach (i.e. inferring properties from molecular structures), 'inverse' QSAR [22,23] modeling (i.e.…”
Section: Machine Intelligence In De Novo Designmentioning
confidence: 99%